Pat in the city : my life of fashion, style, and breaking all the rules - Field, Patricia, 1941-; Paley, Rebecca (Dey St., an imprint of William Morrow, 2023)
From her Studio 54 disco-glam styling to her awarding-winning work in The Devil Wears Prada, Sex in the City, and Emily in Paris, the iconic stylist and fashion provocateur, now in her 70s, tells her story of a life spent challenging conventions.